Peningkatan Hasil Belajar Matematika Menggunakan Contextual Teaching Learning (CTL) Pada Siswa Kelas III SDN 39 Cakranegara Ajaran 2022/2023 - Sukma Wulandari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This study aims to improve students' mathematics learning outcomes using contextual teaching learning in class III SDN 39 Cakranegara, the object of the study consisted of 20 students. This Classroom Action Research uses the John Elliot Model and is carried out in two cycles, each cycle containing two meetings. The data collected is descriptive qualitative data obtained from aspects of student behavior when participating in Mathematics learning. Aspects of student behavior when learning Mathematics were obtained through observation, interviews and student learning tests, based on data collected in cycle I there were 10 students who completed and 10 students did not complete, based on this data the learning outcomes were not in accordance with the success indicators of PTK, the researchers decided to continue cycle II, in cycle II the application was not much different from the first cycle, but at each meeting the researchers always started learning by memorizing multiplication 1 to 10 together, with the addition of this activity the data obtained in cycle II was from 20 people There are only 2 students who have not finished yet. Based on the results of cycle II the teacher decided to stop this research because based on indicators of the success of this PTK it could be categorized as successful because based on a percentage of more than 80%, namely getting 90% success.